Especially exercises for develop agility, and compatibility, and its impact on learning the of transmission reception skill in volleyball for middle school students. - Lefta, Samer (Journal of Physical Education, 2014)
The problem by highlighting the weakness of some motor skills for most students and the lack of attention commensurate with their importance in learning the skill received send by hands from bottom to the intermediate stage students. Included the first chapter on the front of research، in which he discussed Finder volleyball skills and special skill transmitter receiver and the importance that has a learner's level of fitness and compatibility can implement duty motor placed it، as well as the role of scientific research and studies that have contributed to the evolution of volleyball and skills، The second section included topics pertaining to search exercises sports and its importance and special exercises، which included Title research methodology as the researcher used the experimental style of the experimental group equal with the officer، and the sample was selected way intentional's (20) students in the second grade average in the mid-Mahmudiya for Boys was in this door and how they were choosing variables and method of making the experiment Home، Part four has been the search results are displayed and discussed in the light of the results obtained by the researcher due to the experiment for research، and got the researcher then the conclusions and recommendations reached and presented in Section، and it was the most important conclusions improvement in agility and compatibility and positive impact in improving the performance of the skill transmitter receiver، is the most important recommendations to improve the emphasis on agility and compatibility by taking into account the gradient within sports lessons in schools